Gender Reconstruction in Visual Form of Teaching Material - Wening Sahayu; Lia Malia; Retna Endah Sri Mulyati; Sulis Triyono; Rahma Kurnia Novitasari; Sulaimon Jamiu Tamitope (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: Gender has become a crucial area of research due to the unpleasant experience of gender disparity in the workplace, home, and other settings, including education, health, and civic engagement. The ideal way to promote gender equality early on is to guarantee everyone access to a high-quality education. The learning process is greatly aided by textbooks. Through language, visuals, stories, and illustrations, gender content is developed and represented in books. Given that the textbook serves as the primary means of instruction, it is crucial to examine how gender is constructed in Kontakte Deutsch 1, the widely used textbook in Indonesia. Methodology: A descriptive qualitative methodology was used in this study's Critical Discourse Analysis (CDA) approach. The research data source was from illustrations, words, and stories in the textbook Kontakte Deutsch 1. Findings: The results showed that male and female figures appeared visually at the same frequency. In categories like social roles, passions, and professional choices, gender equality was noted and portrayed. Inequalities such as stereotyping, gender subordination, and marginalization of gender were still present in a tiny proportion of phrases and narratives. Conclusion: This study demonstrated how the authors of Kontakte Deutsch 1 made an effort to advance gender equality principles through linked topics. Gender discrimination only appeared in a minor portion of the story. Originality: There have been no studies on gender reconstruction in Kontakte Deutsch 1, commonly used in Indonesian high schools. This thorough investigation deepens our understanding of how gender is portrayed in instructional materials and emphasizes the significance of treating all genders equally and respectfully.